ANALISA KARAKTERISTIK KELERENGAN PANTAI PANGANDARAN TERHADAP TSUNAMI - Maraya Abisurya Patandianan; Ahmad Yasir Baeda; Sabaruddin Rahman (Riset Sains dan Teknologi Kelautan, 2023)
In 2006, the Pangandaran Regency area was hit by a tsunami caused by a tectonic earthquake measuring 7.7 SR. The slope conditions in the Pangandaran Regency area have a percentage value ranging from 0% - 4.59%, with this value the vulnerability value to the impacts of the tsunami will be greater. Looking at the slope of the area will show how the slope value is influenced. The data collection method is through previous data and secondary data. This analytical study can be a reference in considering development planning by understanding the surrounding environmental conditions and disaster history of the area, so as to minimize the impact of disasters. Keywords: Pangandaran Beach, Tsunami, Slope